1979
DOI: 10.2134/jeq1979.00472425000800030005x
|View full text |Cite
|
Sign up to set email alerts
|

Transformations of Carbon, Nitrogen, and Metals in Soils Treated with Waste Materials

Abstract: Intact soil cores were used to evaluate decomposition, NH3 volatilization, N transformations, and metal movement in soils treated with sewage sludges and antibiotic processing wastes. Soil cores were leached monthly with water and incubated for 1 year. An insignificant amount (<1%) of the NH4+‐N applied was lost through NH3 volatilization. The addition of wastes to five soils established that soil properties did not influence decomposition. In contrast, appreciable differences in decomposition were observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
4

Year Published

1981
1981
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…Isto significa que, ao final dos dez primeiros dias de incubação, mais da metade do C o foi liberado na forma de C-CO 2 , evidenciando, assim, uma fase de rápida mineralização, seguida de outra mais lenta e de estabilização dos fluxos de C-CO 2 . Esse comportamento é comum quando se adicionam resídu-os orgânicos a solos agrícolas (Sommers et al, 1979;Bernal et al, 1998).…”
Section: Resultsunclassified
“…Isto significa que, ao final dos dez primeiros dias de incubação, mais da metade do C o foi liberado na forma de C-CO 2 , evidenciando, assim, uma fase de rápida mineralização, seguida de outra mais lenta e de estabilização dos fluxos de C-CO 2 . Esse comportamento é comum quando se adicionam resídu-os orgânicos a solos agrícolas (Sommers et al, 1979;Bernal et al, 1998).…”
Section: Resultsunclassified
“…Some of them showed that the C and N mineralization rates varied with the sewage sludges (7,11,13,15). PARKER and SOMMERS (13) observed that the percentage of sludge N mineralized was related to the concentration of organic N in the sludges.…”
mentioning
confidence: 99%
“…Degradation manifested in decreased TST and induced adverse changes in soil properties, but organic amendments improved soil CEC, total N and organic matter contents and enhanced plant performance. Previous work has demonstrated the agronomic benefits of soil incorporation of organic wastes for the revegetation of degraded soils (Summers et al 1979, Brown et al 1982, Topper & Sabey 1986, Wong & Wong 1989, Chu & Bradshaw 1996. In this study, surface application of topsoil, municipal waste and NPK fertilizer created artificial topsoil layer and/or overcame structural and nutrient stresses in the surface horizon and provided a store of nutrients (organic matter) which through mineralization released nutrients slowly to the nutrient pool and become available for plant uptake.…”
Section: Discussionmentioning
confidence: 88%
“…Biological re-utilization of organic wastes will reduce environmental pollution and enhance landscape appearance (Parr & Papendick 1993). Their suitability nevertheless depends on edaphic properties (Summers et al 1979, Topper & Sabey 1986. Biorestoration of degraded landscapes for environmental protection built on the recruitment of native components of biodiversity will reduce initial and maintenance costs of reclamation process.…”
Section: Introductionmentioning
confidence: 99%